2006
DOI: 10.1099/jmm.0.46609-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Streptococcus mutans in heart valve and dental plaque specimens from a patient with infective endocarditis

Abstract: Streptococcus mutans, known to be an aetiologic agent of dental caries, also causes infective endocarditis (IE), although a comparison of isolates from the oral cavity and infected heart valve of the same patient has not been reported. In the present study, infected heart valve and dental plaque samples from a patient with IE were analysed. Broad-range PCR with DNA sequencing revealed that 50 clones from the dental plaque isolates were composed of oral streptococci and periodontopathic bacteria, whereas only S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 35 publications
1
72
0
10
Order By: Relevance
“…The detection of S. mutans in specimens taken from patients with IE has been reported by either conventional or molecular techniques (Gauduchon et al, 2001;Nakano et al, 2006;Nomura et al, 2006;Vose et al, 1987;Ullman et al, 1988). Since IE is initiated by the colonization of the organism on the ECM of damaged endothelium in heart tissue (Moreillon & Que, 2004), bacterial molecules associated with adhesion to ECM are considered important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of S. mutans in specimens taken from patients with IE has been reported by either conventional or molecular techniques (Gauduchon et al, 2001;Nakano et al, 2006;Nomura et al, 2006;Vose et al, 1987;Ullman et al, 1988). Since IE is initiated by the colonization of the organism on the ECM of damaged endothelium in heart tissue (Moreillon & Que, 2004), bacterial molecules associated with adhesion to ECM are considered important.…”
Section: Discussionmentioning
confidence: 99%
“…Various pieces of evidence show the association of S. mutans with some life-threatening diseases such as infective endocarditis (IE), although the major species related to IE belong to the mitis group of oral streptococci (Banas, 2004;Mylonakis & Calderwood, 2001). Moreover, continuous detections of this bacterium in specimens from patients suffering from such disease emphasize the importance of S. mutans in IE (Gauduchon et al, 2001;Nomura et al, 2006;Vose et al, 1987;Ullman et al, 1988). Indeed, studies to clarify specific components involved in IE in S. mutans have also been performed worldwide (Beg et al, 2002;Jung et al, 2009; MatsumotoNakano et al, 2009;Miller-Torbert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Examination of blood isolates of S. mutans from patients with bacteraemia or IE has been reported in several studies in which alterations of cell-surface components such as serotype-specific polysaccharides or protein antigens were described (Munro & Macrina, 1993;Fujiwara et al, 2001;Chia et al, 2004;Nomura et al, 2006Nomura et al, , 2007Nakano et al, 2007). For GTFs, analysis of an S. mutans isogenic mutant strain with defects in the three types of GTF generated from the blood isolate strain V403 showed that sucrose-derived exopolysaccharides contributed to infectivity in endocarditis caused by S. mutans (Munro & Macrina, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the S. mutans strains used in this study. Strains V1-V7 and P1-P18 were isolated from heart valve and dental plaque specimens, respectively, obtained from an IE patient (Nomura et al, 2006). Strain MT8148 and its isogenic mutant strains defective in GTF expression (S2, R4, DE1, S5, B9, C13 and BC7s) were also used (Ooshima et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation